ENHANCING STUDENTS’ SELF-EFFICACY IN ORAL PRESENTATIONS: A PROPOSED CONCEPTUAL FRAMEWORK FOR SEAMLESS LEARNING ENVIRONMENTS (SLEs) - Chulan, Majdah; Yahaya, Mohamad Fadhili; Shafie , Latisha Asmaak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Self-efficacy in oral presentations is a significant factor in language learning that influences students' communication skill, and academic performance. In seamless learning environments (SLEs), where learning takes place in both formal and informal contexts, many students struggle with low self-efficacy in their oral presentations due to anxiety, lack of practice, fear of negative evaluation and insufficient feedback. They may also not be exposed to digital tools usage which limits their opportunities for their reflective learning and presentation skill development. These feelings may reduce their confidence and willingness to do their oral presentations even though they have good content knowledge. This conceptual paper explores the challenges students face in developing their self-efficacy, and the role of seamless learning environments (SLEs) in enhancing students’ presentation skills. Thus, an in-depth literature review was conducted related to students’ self-efficacy and their oral presentations in a seamless learning environment (SLE). Furthermore, a conceptual framework that incorporates self-efficacy theory, students’ oral presentations, digital tool usage and seamless learning environment (SLE) is proposed for further exploration. The purpose of the framework is to improve students’ self-efficacy in delivering oral presentations in a seamless learning environment (SLE). It further emphasises the importance of combining both theoretical viewpoints and the existing literature. Apart from that, it also offers experiential learning, personalized feedback, peer collaboration, and emotional support which promote a supportive learning environment for students to develop their oral presentation skills and overcome their self-efficacy barriers.